Amino-functionalized zr-based metal-organic tetrahedron for adsorptive removal of sulfonamide antibiotic in aqueous phase. (1st January 2022) - Liu, Zhao-Yang; Tong, Ruo-Ming; Chen, Xin; Zhang, Yu-Teng
Graphical abstract: The adsorption performances of amino-functionalized Zr-based metal-organic tetrahedron (ZrT-1-NH2 ) for sulfachloropyridazine (SCP) in aqueous solution were first reported. Abstract: An amino-functionalized Zr-based metal–organic tetrahedron (denoted as ZrT-1-NH2 ) was synthesized under solvothermal conditions. In addition, the adsorption performances of ZrT-1-NH2 for sulfachloropyridazine (SCP) from aqueous solution were investigated. Moreover, the experimental results revealed that ZrT-1-NH2 has adsorption performance for SCP. The adsorption kinetic data were best fitted with the pseudo second order model. Furthermore, a plausible adsorption mechanism was proposed.